Economic Analysis of the Use of Tourists on Tourism Objects in Makassar City - Dahliah Dahliah (Jurnal Economic Resource, 2021)
This study's first objective is to analyse tourists' use to increase the income of tourist objects in Makassar City. To accelerate and strengthen economic development following the potential advantages of marine tourism, accelerate growth by supporting tourism, namely developing government programs in the tourism sector. To take advantage of the potential and utilization of tourists to increase community income in marine tourism objects. The goals and targets to be achieved in long-term research are. This study's results can contribute to and support the use of tourists for research on increasing income in marine tourism objects so that they contribute to improving the revenue of maritime tourism objects.